Knowledge Graph Analysis of Tai Chi in Global Clinical Intervention Research (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Objective: This study aims to elucidate the current state of research, identify leading areas of interest, and forecast the evolving trends in Taijiquan clinical intervention research. Additionally, it seeks to advance the scientific, standardized, and health-oriented development of Taijiquan clinical intervention research. By employing knowledge mapping and multivariate data analysis techniques, this research offers both qualitative and quantitative insights into the dynamic landscape of international Taijiquan clinical intervention research. The results provide a comprehensive overview of the field and serve as a valuable reference for future studies. Methods: This study focused on clinical intervention research related to Taijiquan, spanning up to 75 years, using mainstream Chinese and English databases as its primary data sources. The research methodology employed Price's scientific literature logical growth curve theory to facilitate a temporal and spatial evolution analysis of the literature retrieved from Chinese and English databases. Additionally, various bibliometric visualization software tools, in conjunction with state-of-the-art analytical methods, were utilized to construct scientific knowledge maps. These maps were subjected to interpretation, ranging from a macroscopic view to a microscopic one, from intuitive to intricate, and from comprehensive to selective. Through a layered approach, in-depth analysis was conducted to visually present a panoramic view of the clinical intervention research field of Taijiquan. This process systematically elucidated the research status, identified frontier hotspots, and forecasted research trends within the domain. Results: In the current research landscape, Taijiquan research within the CNKI Chinese database exceeds that within the WOS English database by a factor of four. However, in the realm of Taijiquan clinical intervention research, the WOS English database surpasses the CNKI Chinese database by a factor of three, with a sixfold higher representation of high-quality research. This suggests that there is still untapped potential for growth within the CNKI Chinese database and Chinese research related to the health and scientific aspects of Taijiquan. It is possible that Chinese research may encounter a bottleneck in paradigm accumulation, necessitating either theoretical innovation or technological advancement to overcome potential scientific challenges. According to Price's logical growth curve, Taijiquan clinical intervention research in the WOS English database is approaching the culmination of exponential growth associated with conventional scientific stages. To prepare for potential scientific challenges in the future, proactive utilization of theory to guide practice and the completion of paradigm accumulation is imperative. Striving to explore new paradigms to drive paradigm shifts, breaking bottlenecks to facilitate scientific revolutions, and leading new conventions in science are essential objectives. As one of the earliest countries engaged in clinical intervention research on Taijiquan, the United States publishes twice as many articles as China in this domain, with double the citation impact. This discrepancy may be attributed to the overall development of its scientific research landscape and the high level of innovation in its scientific research theories. Taijiquan benefits from a more fertile environment for dissemination within Asian cultural circles. In addition to cultural studies, there is untapped potential for further exploration in the realm of health applications for clinical interventions involving Taijiquan. The fields of basic research encompassed within Taijiquan clinical intervention research are notably multifaceted, with medicine, neurology, psychology, and other disciplines forming the core research focus, leading the frontier. Rehabilitation, nursing, biology, and related fields provide the foundational support for these investigations. Given the ongoing expansion and deepening of interdisciplinary research, the coverage of discipline groups within the realm of Taijiquan clinical intervention research is poised to become even more extensive. Regarding research hotspots, the basic research fields within the domain of Taijiquan clinical intervention research are indeed intricate, with medicine, neurology, and psychology driving the forefront of research interest, while rehabilitation, nursing, biology, and related disciplines underpin the foundational research. Emerging themes can be categorized into three distinct stages, each highlighting research progression from the motor system to the nervous system and ultimately to the complex multi-system approach. Taijiquan itself can be classified into various modes, including confrontation, exercise, and treatment, with the simplified 24-style Taijiquan emerging as the most commonly utilized low-intensity aerobic exercise mode in current clinical intervention routines. Conclusion: Visual analysis reveals that international clinical intervention research on Taijiquan has experienced exponential growth, with a concurrent increase in high-quality research. Nevertheless, several challenges persist, and there remains untapped potential within the CNKI Chinese database and Chinese research related to the health and scientific aspects of Taijiquan. It is possible that Chinese research may encounter a bottleneck in paradigm accumulation, necessitating either theoretical innovation or technological advancement to overcome potential scientific challenges. Proactive utilization of theory to guide practice, the completion of paradigm accumulation, and readiness for potential scientific crises are essential. Striving to explore new paradigms to drive paradigm shifts, breaking bottlenecks to facilitate scientific revolutions, and leading new conventions in science are critical objectives. Taijiquan is culturally rooted in Asian circles, offering ample opportunities for dissemination. Beyond cultural studies, there is untapped potential for further exploration in the realm of health applications for clinical interventions involving Taijiquan. With ongoing extensive and deepening interdisciplinary research, the coverage of discipline groups within the Taijiquan clinical intervention research field is poised to expand further. Predictive burst intensity analysis suggests that research enthusiasm on cancer-related topics may fluctuate in the future, while the popularity of research on subjects like diabetes and hypertension may remain relatively stable. Future research hotspots are expected to focus on the nervous system, including areas such as anxiety and sleep. If aimed at treatment, it is imperative to enhance practicality and innovation by developing concrete, standardized, and differentiated Tai Chi treatment models, harnessing its potential for clinical intervention. Furthermore, efforts should be directed towards strengthening interdisciplinary integration, fostering international collaboration, and securing financial support. These measures will aid in enhancing the quality of clinical intervention research on Taijiquan and obtaining more long-term, large-sample-sized, and highly targeted clinical evidence.